Polycythemia vera is a medical condition characterized by raised hematocrit. Owing to increased viscosity, the blood flow in the vessels become sluggish leading to the clinical features of polycythemia such as headache, blurring of vision, red skin, dizzi - Nabeela Iqbal; Syed Khalid Shah; Shamima Haneef (Journal of Bahria University Medical and Dental College, 2021)
Polycythemia vera is a medical condition characterized by raised hematocrit. Owing to increased viscosity, the blood flow in the vessels become sluggish leading to the clinical features of polycythemia such as headache, blurring of vision, red skin, dizziness, raised blood pressure, itching and more serious medical events like vaso occlusion, thrombosis and strokes. In this case report, polycythemia vera presenting unusually with heamatemesis, melena and abdominal distension. Physical examination of this case revealed massive ascites with dilated veins around the umbilicus. The diagnosis of polycythemia vera complicated by Budd Chiari Syndrome and Portal Vein Thrombosis was made. Patients with polycythemia vera are at risk of vaso occlusive sequelea like portal vein thrombosis and Budd chiari syndrome.